The Psychological Basis of Aesthetic Preferences: Insights from Facial Attractiveness and Architectural Appreciation - HO, PIK KI (Trinity College Dublin. School of Psychology. Discipline of Psychology, 2020)
Aesthetic experience is personal and yet universal. It has long been an intriguing subject of interest for philosophers and psychologists alike. Though even without consciously contemplating beauty, our aesthetic preferences influence many of our day- to-day choices beyond pure hedonism – from purchase decisions of products, selecting a partner, to voting behaviour in elections; all of which have real-world consequences. The main goal of the research described in this thesis was to advance empirical understanding of the factors that influence aesthetic judgements. The research focussed on of two ubiquitous categories of stimuli in our visual world, human faces and built environments. As such, this thesis consists of two main themes, facial attractiveness and architecture appreciation. First impressions are thought to be formed within fractions of a second when seeing an unfamiliar face. Some researchers even argue that facial attractiveness judgements occur in a mandatory manner alongside other aspects of face processing, even when attractiveness is irrelevant to the task at hand. Once formed, these judgements persist and are difficult to inhibit. It has long been established that a number of invariant, or unchangeable facial features such as symmetry, averageness, and sexual dimorphism play a role in attractiveness. However, mounting evidence has shown that transient, or changeable facial properties such as gaze direction, head orientation and facial expression also modulate perceived attractiveness. For instance, faces which display a combination of a direct eye gaze at the observer and happy expression are known to be perceived as more attractive than those with an averted gaze and negative expression (e.g. sad or angry). These effects and their possible causal effects are described in Chapter 1. It is unclear, however, whether different social cues to attractiveness affect those judgements in an integrated or independent manner. Moreover, previous studies on facial attractiveness might not reflect typical social interactions in which gaze direction, head orientation and facial expression are constantly changing. As such, the first question addressed in this thesis, and described in Chapters 2 and 3, concerns the role of dynamic social cues and their interaction on facial attractiveness. Specifically, the study described in Chapter 2 investigated whether the effect of facial expression on attractiveness was modulated by a dynamic gaze shift; and the study in Chapter 3 investigated the role of head turns. The second question addressed in the issue of serial dependency in which the rating provided to the stimulus in the current trial may be affected by the rating provided in the previous trial in a manner that is distinct from a response bias. The study described in Chapter 4 tested whether serial dependency occurs both within and across categories of stimuli (faces vs. built environments) in aesthetic rating tasks. Serial dependency was found in aesthetic judgements thus expanding previous findings of serial dependency in perception to higher levels of visual interpretation. Unlike facial attractiveness, in which faces are an important social stimulus, aesthetic judgements for architecture appears to show greater individual differences. Nevertheless, some features appear to universally enhance aesthetic preferences in objects and scenes. The study described in Chapter 5 examined the effects of visual features, such as curvature, on the aesthetic judgements of architecture (both outdoor and indoor). Furthermore, the role of personality dimensions on these judgements was also investigated. Finally, in Chapter 6, the role of eye movements was investigated to determine regions of interest when participants are required to aesthetically evaluate exterior images of buildings. A summary of the findings and their implications are discussed in detail in Chapter 7. The overall findings of this thesis have demonstrated that facial attractiveness judgements are affected by a combination of factors, including social (e.g. expressions and eye gaze) as well as visual (particularly dynamic changes). Moreover, aesthetic preferences in architecture are determined by both visual properties of the buildings such as curvature, ceiling height, window-to-wall ratio, as well as personality traits of the observer. The thesis argued that in order to gain deeper understanding of aesthetic processing, more ecologically valid paradigms and stimuli are required (e.g. real models for facial attractiveness, and full immersion in 3D environments for architecture appreciation) that reflect better the real-world scenario of aesthetic evaluation. Recent technological advancements in virtual reality and mobile eye tracking offer promising avenues for future research on the topic.
APPROVED
Keywords: Empirical aesthetics; Visual aesthetics; Facial attractiveness; Architectural aesthetics; Experimental psychology